2018
DOI: 10.1029/2018jd028889
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Enhanced Heterogeneous Ice Nucleation in Simulated Deep Convective Clouds Observed During DC3

Abstract: The impacts of enhanced heterogeneous ice nucleation (HET) on the properties of deep convective clouds (DCCs) have been investigated in cloud-resolving simulations with the WRF-CHEM model. The study focuses on a case observed during the Deep Convective Clouds and Chemistry (DC3) field campaign. For the simulated DCCs, which had cold cloud-base temperatures, an inverse relationship exists between ice crystal mass produced through HET and anvil ice crystal number concentrations. This seems to be due to the indir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 79 publications
0
20
1
Order By: Relevance
“…Most of the droplet activation naturally takes place near cloud base where supersaturation maximizes, and hence additional particles at high altitudes only weakly affected droplet number concentrations (i.e., most of the cloud droplets must have been activated below and lifted upward). This finding suggests that the observed injection of the smoke plume into the DCCs likely had a small impact on droplets relative to its high particle number concentrations, although it might have had an influence on ice nucleation (e.g., Takeishi & Storelvmo, 2018). This effect of aerosols as INPs is beyond the scope of this study.…”
Section: Fire Impacts On the Microphysical Characteristics Of The Dccsmentioning
confidence: 85%
“…Most of the droplet activation naturally takes place near cloud base where supersaturation maximizes, and hence additional particles at high altitudes only weakly affected droplet number concentrations (i.e., most of the cloud droplets must have been activated below and lifted upward). This finding suggests that the observed injection of the smoke plume into the DCCs likely had a small impact on droplets relative to its high particle number concentrations, although it might have had an influence on ice nucleation (e.g., Takeishi & Storelvmo, 2018). This effect of aerosols as INPs is beyond the scope of this study.…”
Section: Fire Impacts On the Microphysical Characteristics Of The Dccsmentioning
confidence: 85%
“…Simulations of the 22 June 2012 Colorado severe storms using WRF‐Chem at Δx = 1 km found that storms with cold cloud bases and therefore small contributions of the warm‐rain processes to precipitation caused enhanced heterogeneous ice nucleation compared to the homogeneous ice nucleation process. When heterogeneous ice nucleation was enhanced, the storm anvils were optically thinner (Takeishi & Storelvmo, ).…”
Section: Findings From Dc3mentioning
confidence: 99%
“…It is known from model simulations that changes in INP number concentration affect the microphysical properties and behaviour of deep convective clouds (Deng et al, 2018;Fan et al, 2010aFan et al, , 2010bGibbons et al, 2018;Takeishi and Storelvmo, 2018). However, in these model studies perturbations to INP number concentrations have predominantly involved uniform increases in aerosol or INP concentrations with all simulations using the same INP parameterisation (Carrió et al, 2007;Connolly et al, 2006;Deng et al, 2018;Ekman et al, 2007;Fan et al, 2010a;Gibbons et al, 2018;van den Heever et al, 2006;Phillips et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…However, in these model studies perturbations to INP number concentrations have predominantly involved uniform increases in aerosol or INP concentrations with all simulations using the same INP parameterisation (Carrió et al, 2007;Connolly et al, 2006;Deng et al, 2018;Ekman et al, 2007;Fan et al, 2010a;Gibbons et al, 2018;van den Heever et al, 2006;Phillips et al, 2005). Where different INP parameterisations have been used (Eidhammer et al, 2009;Fan et al, 2010b;Liu et al, 2018;Takeishi and Storelvmo, 2018), the results have in most cases been interpreted in terms of the overall increase in INP number concentration (Fan et al, 2010b;Liu et al, 2018;Takeishi and Storelvmo, 2018). However, there are important structural differences between different INP parameterisations that have not yet been explored in detail.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation